Speed and Convulsive Beauty: Trains and the Historic Avant-garde - Marylaura Papalas (Studies in 20th & 21st Century Literature, 2015)
The train, an invention and evocative symbol of the 19th century, somewhat ironically continued to fascinate avant-garde artists and writers of the 20th century, when faster and more exciting modes of transportation were in use. Locomotive imagery in Italian futurism and French surrealism, however, demonstrates a lasting fascination with speed, locomotive space, and their effect on perceptions of reality. Considering the work of more recent theorists like Paul Virilio, Michel Foucault, and various others who have contributed to the growing field of mobility studies, this paper aims to understand the persisting presence of the train as a symbol of an alternative reality in historic avant-garde work, particularly that of the Italian Futurists and the French Surrealists.
Keywords: Avant-garde; Train; Locomotive Imagery; Speed; Mobility Studies; Futurism; Blaise Cendrars; Surrealism; Modernity; European Literature